Magnetoelastic coupling and phases in the skyrmion lattice magnet Gd2PdSi3 discovered by high-resolution dilatometry - Spachmann, Sven; Elghandour, Ahmed; Frontzek, M.; Löser, W.; Klingeler, Rüdiger (Physical review, 2021)
We report detailed thermodynamic studies on high-quality single crystals of the centrosymmetric skyrmion-hosting intermetallic Gd2PdSi3 by means of high-resolution capacitance dilatometry in fields up to 15 T which are complemented by specific heat and magnetization studies. Our dilatometric measurements show magnetoelastic effects associated with antiferromagnetic order at TN1=22.3 K and TN2=19.7 K, as well as strong field effects in an applied magnetic field of 15 T up to 200 K (150 K) for B∥c (B∥a*, i.e., B⊥c). The data allow us to complete the magnetic phase diagram, including a feature at T∗≈13K below which an additional degree of freedom becomes relevant. The magnetic B vs T phase diagram for the a* axis is also reported. Grüneisen analysis shows the onset of magnetic contributions around 60 K, i.e., well above TN1. Uniaxial pressure dependencies of opposite signs, −1.3 and 0.3 K/GPa, are extracted for the out-of-plane and in-plane directions at TN1. For T∗ we obtain ∂T∗/∂pc=1.4 K/GPa. In particular we elucidate thermodynamic properties of the recently discovered skyrmion lattice phase and show that it is strongly enhanced by uniaxial pressure.